An efficient organic inverted solar cell with AnE-PVstat:PCBM active layer and V2O5/Al anode layer - Kösemen, Arif; Tore, Nesrin; Parlak, Elif Alturk; Kosemen, Zuhal Alpaslan; Ulbricht, Christoph; Usluer, Ozlem; San, Sait Eren (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
An inverted organic solar cell, which is based on anthcene-containing poly (p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) (PPE-PPV) polymer (AnE-PVstat) and phenyl C-61 butyric acid methyl ester (PCBM), was fabricated with Titanium dioxide (TiO2) electron transport layer and V2O5/Al anode layer. In this study, we have investigated the effect of V2O5 thickness on solar cell efficiency. Power conversion efficiency of 3.26% has been achieved for 15 nm V2O5 layer. The lifetime of the cell was investigated using ISOS-L-1. The test indicated that the durability of the solar cell, which is designed in ITO/TiO2/AnE-PVstat:PCBM/V2O5 (15 nm)/Al configuration, is 99% under standard solar irradiation of 100 mW/cm(2) (AM 1.5 G) at ambient conditions for 24 h. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Inverted organic solar cell; V2O5 anodic buffer layer; PPE-PPV; AnE-PVstat; TiO2